Attentional bias and metacognitions in cancer survivors with high fear of cancer recurrence. Issue 4 (25th August 2014) - Butow, P.; Kelly, S.; Thewes, B.; Hruby, G.; Sharpe, L.; Beith, J.
Abstract Background Fear of cancer recurrence (FCR) is a common and severe problem amongst cancer survivors, but mechanisms to explain its development and maintenance are still lacking. The self‐regulatory executive function (S‐REF) model suggests that metacognitions and attentional bias to cancer‐related words may explain high FCR. Thus, this study aimed to explore relationships between FCR, metacognitions and attentional bias in a mixed group of cancer survivors. Method Sixty‐three early‐stage breast or prostate cancer survivors, diagnosed within 6 months to 5 years prior to participation and who had completed all hospital‐based treatment with no evidence of cancer recurrence were recruited through two metropolitan oncology clinics. Participants completed a questionnaire battery and the dot‐probe task. Results Survivors with clinical FCR had significantly greater positive beliefs about worry (10.1 vs 7.4, p = 0.002) and beliefs about the uncontrollability and danger of worry (12.0 vs 7.7, p = 0.000) than those with non‐clinical FCR, whereas the total metacognition score significantly predicted FCR in multiple regression analysis (β = 0.371, p = 0.001). No significant differences were detected between participants scoring above and below clinical FCR levels in attention bias indices. Conclusions This study found partial support for the S‐REF model of FCR, with metacognitions but not attentional bias found to be related to FCR. Further research is needed to explore attentional biases in more detail. Copyright © 2014 John Wiley & Sons, Ltd.